Tuesdays with Morrie : an old man, a young man, and life's greatest lesson - Albom, Mitch (New York : Anchor Books, 1997)
A memoir about weekly conversations between the author and his former professor Morrie Schwartz, discussing life lessons while Schwartz battles ALS.
Keywords: Schwartz, Morrie; Mentors -- Biography; Death -- Psychological aspects